Being a physician in the military environment, triage and ethical dilemmas [Askeri ortamda hekimlik, triyaj ve etik ikilemler] - (:unkn) unknown (My University, 2006)
Triage is defined as "The classification of the patients according to the types of their light sickness and wounds", "The classification of the wounds after the first medical treatment of the patients and the activities aiming to cure the patients as soon as possible at the nearest health organization", "During the circumstances when there are many patients and wounded people, rapid choosing and coding process, at the place of the event and at the health organization where the patients are transported, aiming to realize the transferring and the medical treatment of these patients and wounded people first". Systematic and productive using of the medical sources is aimed with this point of view. In the applications of the physicians in the military environment, triage and ethical dilemmas may vary. The physician may experience internal conflict between a desire to protect the patient from additional trauma and the duty to support the needs of the needs of the command. This is the classical mixed agency issue. Another ethical dilemma in the battlefield triage applications is: How far can a military physician go in the course of making decisions in the best interest of the patient? In the battlefield triage, it is expected from the physician to realize what is best for the soldier's own good. Between several medical ethical conflicts in the battlefield health applications, these are also discussed; 1. Conflict between the military obligation of the physicians and other medical personnel to provide care to members of the military force of which they are members and the medical obligation to serve others-such as members of opposing military forces and civilians- who need their care. 2. Conflict between the obligation of military medical personnel to "conserve the fighting strength" and the medical obligation to respond to the special needs or rights of individual military personnel under their care, even if such response hinders the "fighting strength". strength".